2017
DOI: 10.5897/ajmr2016.8392
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous fungi isolated from three locoweed species from rangeland in western China

Abstract: Leguminous locoweeds cause toxicosis to grazing animals in western China and western USA. Swainsonine, a toxic alkaloid, is produced by the endophytic fungus Alternaria section Undifilum sp. living within the locoweed plants. Nothing is known of the other endogenous fungi associated with locoweed and it is unknown if the presence of Alternaria sect. Undifilum sp., a potential mutualist, in a locoweed influences the fungal microbiome associated with the plant. To help address these questions, endogenous fungi a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Sequence alignment of the digested bands suggested those partially digested amplicons represented both the A. oxytropis ITS sequence (Figure S5) and the chloroplast sequence and was, therefore, considered an A. oxytropis -positive plant. In all the 90 samples sequenced, no other Alternaria species were identified despite their high genetic homology to A. oxytropis [35]. Infection rates reflected the number of infected individuals as a proportion of the total number of plants in each accession.…”
Section: Methodsmentioning
confidence: 99%
“…Sequence alignment of the digested bands suggested those partially digested amplicons represented both the A. oxytropis ITS sequence (Figure S5) and the chloroplast sequence and was, therefore, considered an A. oxytropis -positive plant. In all the 90 samples sequenced, no other Alternaria species were identified despite their high genetic homology to A. oxytropis [35]. Infection rates reflected the number of infected individuals as a proportion of the total number of plants in each accession.…”
Section: Methodsmentioning
confidence: 99%
“…Since locoweeds hosting A. oxytropis do not show any adverse symptoms, the relationship between locoweed and A. oxytropis are non-parasitic and possibly mutualistic similar to the grass/Epichloë system. The Alternaria section Undifilum species may help to prevent other D r a f t pathogenic fungi or microorganisms from plant invasion (Zabalgogeazcoa 2008;Martinuz et al 2012;Lu et al 2017). In addition, the endophyte may prevent other pathogenic infection by utilizing available nutrients and niches.…”
Section: Discussionmentioning
confidence: 99%
“…Undifilum is present in the soil remain unambiguous. Lu et al [21] isolated several fungi from the soil locoweeds grew, and although those fungi produce swainsonine they did not belong to A. sect. Undifilum.…”
Section: Propagation and Reproduction Of A Sect Undifilummentioning
confidence: 99%
“…However, recent studies showed that A. sect. Undifilum might help their locoweed hosts against pathogens [21], or regulate the endophytic fungi assemblage [22]. Therefore, the ecological role of locoweed symbiosis awaits further investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation